Natural Compounds That Activate the KEAP1/Nrf2 Signaling Pathway as Potential New Drugs in the Treatment of Idiopathic Parkinson's Disease - Sandro Huenchuguala; Juan Segura-Aguilar (MDPI AG, 2024)
Recently, a single-neuron degeneration model has been proposed to understand the development of idiopathic Parkinson's disease based on (i) the extremely slow development of the degenerative process before the onset of motor symptoms and during the progression of the disease and (ii) the fact that it is triggered by an endogenous neurotoxin that does not have an expansive character, limiting its neurotoxic effect to single neuromelanin-containing dopaminergic neurons. It has been proposed that aminochrome is the endogenous neurotoxin that triggers the neurodegenerative process in idiopathic Parkinson's disease by triggering mitochondrial dysfunction, oxidative stress, neuroinflammation, dysfunction of both lysosomal and proteasomal protein degradation, endoplasmic reticulum stress and formation of neurotoxic alpha-synuclein oligomers. Aminochrome is an endogenous neurotoxin that is rapidly reduced by flavoenzymes and/or forms adducts with proteins, which implies that it is impossible for it to have a propagative neurotoxic effect on neighboring neurons. Interestingly, the enzymes DT-diaphorase and glutathione transferase M2-2 prevent the neurotoxic effects of aminochrome. Natural compounds present in fruits, vegetables and other plant products have been shown to activate the KEAP1/Nrf2 signaling pathway by increasing the expression of antioxidant enzymes including DT-diaphorase and glutathione transferase. This review analyzes the possibility of searching for natural compounds that increase the expression of DT-diaphorase and glutathione transferase through activation of the KEAP1/Nrf2 signaling pathway.